1987
DOI: 10.1200/jco.1987.5.10.1574
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin (CBDCA, JM-8) and VP-16-213 in previously untreated patients with small-cell lung cancer.

Abstract: The efficacy and toxicity of carboplatin 100 mg/m2, administered intravenously (IV) daily X 3, and VP-16-213 120 mg/m2, IV daily X 3, administered every 28 days for six courses, was assessed in 94 (36 limited stage, 58 extensive stage) previously untreated patients with small-cell lung cancer. Mediastinal irradiation using 50 Gy in 25 fractions was given to all limited-stage patients with a complete (CR) or partial response (PR) after three chemotherapy courses. Cranial irradiation was administered to all pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(30 citation statements)
references
References 12 publications
2
26
1
1
Order By: Relevance
“…The response rate and survival data for this pilot trial are similar to those from other reported series using platinum/etoposide and doxorubicin-based regimens (Ellis et al, 1995b;Bishop et al, 1987;Evans et al, 1988;Fukuoka et al, 1991;Roth et al, 1992). There was no survival difference between patients entered in this trial and matched controls treated in a series of chemotherapy trials with data entered prospectively on our database (Figure 2).…”
Section: Discussionsupporting
confidence: 71%
“…The response rate and survival data for this pilot trial are similar to those from other reported series using platinum/etoposide and doxorubicin-based regimens (Ellis et al, 1995b;Bishop et al, 1987;Evans et al, 1988;Fukuoka et al, 1991;Roth et al, 1992). There was no survival difference between patients entered in this trial and matched controls treated in a series of chemotherapy trials with data entered prospectively on our database (Figure 2).…”
Section: Discussionsupporting
confidence: 71%
“…Phase II studies of the combination of carboplatin and etoposide for untreated SCLC were initially reported in 1987. 27,28 The efficacy of carboplatin and etoposide combination therapy for untreated SCLC is indistinguishable from that of cisplatin and etoposide, with equivalent response rates and survival duration in randomized comparisons. 29,30 Oblimersen dose levels evaluated in the phase I study included 5 and 7 mg/kg/d.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, carboplatin has been given successfully at doses up to 1600 mg m-2 without substantial toxicity other than bone marrow suppression Shea et al, 1989) The dose achieved in low risk patients compares favourably with that achieved in several phase I-II studies using this combination administered systemically. Bishop et al (1987) evaluated the efficacy and toxicity of carboplatin (100 mg m-2) and etoposide (120 mg m-2) administered intravenously daily for 3 days in 94 patients with previously untreated small cell lung cancer. According to the Common Toxicity Grading Scale, Grade 3 or 4 neutropenia and thrombocytopenia occurred in 63% and 20% of patients respectively.…”
Section: Pharmacokineticsmentioning
confidence: 99%